Calf and Heifer Feeding and Management - Cao, Zhijun; Van Amburgh, Michael (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
From birth to first calving, the replacement heifer undergoes tremendous changes anatomically as well as in feeding and management practices. The calf changes from being a pseudo-monogastric to a full ruminant within a period of two months. During the same period, the calf is fed colostrum, milk, or milk replacer, and starter with or without hay. Notably, the lifetime milk production and health of a dairy cow is highly dependent on early life nutrition and management of the calf and, subsequently, the heifer. Hence, animal scientists continue to investigate critical areas such as colostrum feeding, the level of liquid feeding, gut microbial succession, energy and protein levels, housing, health management, and their interactions with the animal in an effort to help dairy producers raise successful and sustainable dairy enterprises.